When a T cell engages a B cell: novel insights in multiple sclerosis (Swiss Medical Weekly, 2020)
Multiple sclerosis is an autoimmune disease of the central nervous system (CNS) in which autoreactive T cells are considered to be the major effector cells in orchestrating and promoting CNS injuries. However, B cells emerged as additional important cellular player in multiple sclerosis immunopathogenesis since B cell depletion therapy has been found to be very effective in reducing new relapses. This short review summarises important new insights into the interaction between these two cell populations and outlines recent observations regarding how memory B cells activate brain-homing autoreactive T cells in multiple sclerosis.